Analisis Permintaan Masyarakat Mamuju Terhadap Jasa Pengiriman Paket Pada Pt. Pos Indonesia (Persero) Cabang Mamuju - Rafik, Anugerah Nurrezqy; Furqan, Furqan; Rusli, Rusli (Paradoks : Jurnal Ilmu Ekonomi, 2025)
Pos Indonesia (Persero) is a state-owned company, this company has been known by the public as a means of communication and also provides delivery services. This study uses quantitative data, typesof data that can be measured or can be calculated directly, in the form of information or explanation expressed by numbers or in the form of numbers.The sourceof data usedin this study is primary Data is a source of research data obtained directly from the original source (not through intermediaries).There are100 samplesin this study werethen processe dusing SPSS 23 and analyze dusing regression model sand inferential statistics with four tests, namely : 1) classical assumption Test 2) hypothesis test 3) multiple linear regression analysis 4) coefficient of determination analysis (R2). The research results obtained: Variable Delivery Speed, Delivery Rates and Service Quality simultaneously affect the Demand for Package Delivery at PT. Pos Indonesia (Persero) Mamuju Branch. Delivery speed has a positive and significant effect on the Mamuju community's demand for package delivery services at PT. Pos Indonesia (Persero) Mamuju branch. Delivery rate variables have a positive and significant effect on Mamuju people's demand for package delivery services at PT. Pos Indonesia (Persero) Mamuju branch. Service quality variables have a positive and significant effect on Mamuju people's demand for package delivery services at PT. Pos Indonesia (Persero) Mamuju branch. PT. Pos Indonesia (Persero) Mamuju branch has a very big influence on the people of Mamuju city because the presence of the post office makes it easier for people to send letters and packages. From the research results the authors also found the results of 59.6% of the Dependent variable (Demand for package delivery) can be explained by the independent variables, namely: Delivery Speed (X1), Delivery Rates (X2), and Service Quality (X3) while the remaining 40.4% is explained by variables not included in this study.